When Maria Cinta Balagué broadcasted the first radio magazine - Espinosa Mirabet, Sílvia (Historia y Comunicación Social, 2014)
This paper will reveal who was the first radio broadcaster of Catalonia and what were her contributions to the medium. Maria Cinta Balagué, a cultured and conservative woman, developed the first radio magazine when in the early 20s all were monologues and lectures in a catalan radio stations. It happened in Barcelona in a feminine program.
Keywords: Radio; speaker; magazine; history.